1979
DOI: 10.1051/jphyscol:19792200
|View full text |Cite
|
Sign up to set email alerts
|

THE ISOMER SHIFT VALUES OF IMPLANTED /133Xe/133Cs IN VARIOUS HOSTS

Abstract: The isomer shift values of 133Cs implanted in graphite, diamond, Te, Si, Ge, Cu, Zn, Mo, and W are found in a larger interval than those found in Cs and Cs-compounds. The extension to larger values are explained by the increase of electron densities due to the compression of the oversized implanted atom

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From the systematic isomer-shift studies on 133 Cs, it is unlikely to find isomer shifts larger than ϩ0.1 mm/s with respect to a CsCl absorber. [1][2][3]11 Moreover, Campbell, Montet, and Perlow 12 have shown that the quadrupole splitting e 2 qQ ex (Q ex ϭ Ϫ0.22 barn͒ of the 81 keV ͑ 5/2 ϩ ) state in 133 Cs is not negligible; it can be measured by Mössbauer spectroscopy for sufficiently large field gradients. Thus, the line at positive velocity in the spectrum belongs to a quadrupole triplet which has a reasonable isomer shift.…”
Section: Experimental Results and Data Analysismentioning
confidence: 99%
“…From the systematic isomer-shift studies on 133 Cs, it is unlikely to find isomer shifts larger than ϩ0.1 mm/s with respect to a CsCl absorber. [1][2][3]11 Moreover, Campbell, Montet, and Perlow 12 have shown that the quadrupole splitting e 2 qQ ex (Q ex ϭ Ϫ0.22 barn͒ of the 81 keV ͑ 5/2 ϩ ) state in 133 Cs is not negligible; it can be measured by Mössbauer spectroscopy for sufficiently large field gradients. Thus, the line at positive velocity in the spectrum belongs to a quadrupole triplet which has a reasonable isomer shift.…”
Section: Experimental Results and Data Analysismentioning
confidence: 99%
“…Three more experiments can be quoted to support this assignment. First, an implantation of 133Xe in pyrolytic graphite yields a single absorption line at 0.03 ± 0.05 mm/s [47]. Moreover, we have performed a hot implantation of 133Xe at 1014 at/cin2 and 600°C; we also did a room temperature implantation at the same dose, followed by thermal annealing in vacuo « 2 x 10-' torr) at 1 100 OC.…”
Section: Laser and Thermal Annealing Of Te-implantedmentioning
confidence: 99%